Help for the terminally ill and the dispute over the permissibility of euthanasia - Stępa, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Currently, there is an observable global phenomenon of aging societies, which is associated with the extension of human lives. However, a longer life is one of the reasons for the recording of a growing population affected by “terminal diseases”. These include malignant tumours (neoplasmamalignum)1 and AIDS2. The late stages of these diseases include the appearance of paresis, paralysis3 , aphasia, dementia, and coma. Similar symptoms are observed in the case of neurological conditions such as: 1. Alzheimer's disease; 2. cerebral haemorrhages; 3. brain oedema6; 4. multiple sclerosis7and post-trauma (accident), which means that these may be added to thediseases thatrequire a similar procedure as in the caseof the aforementioned.People suffering from these require specialised treatment and care. Thisinvolves considerable financial outlay bythe state (research, treatment). Inaddition, the economy isunusually burdened by factors such as: care allowances to be paid, employment of qualified staff, and the creation of appropriate assistance centres. The search for budget reserves forthis social groupencounters insurmountable obstacles. At the same time,the existing focus onproductive people (laws of economics)causesa lack of perception and a lackofwillingness to addressthe chronically ill at theend oftheirlives,orthe terminally ill8, putting up barriers to them (lack of funding for hospices,palliativewards, and care allowances). In view of thegrowing demographicand earnings problemswe are increasingly confrontedwithpseudo-rationalclaims to alloweuthanasia(from the Greek meaninggood death), contrary tonatural law.It has been accepted that this is defined as the compassionate killing of someone who is suffering and terminally ill. Euthanasia is to be carried out in the name of the “human freedom” to decide for ourselves, but also to interrupt the pain or end the suffering in a phase in which nothing more can be done (resulting in death). From time to time, various countries are swept by a wave of discussion about its permissibility, and this dispute has been going on for centuries. The aim of the study is not only to approximate the size of the problem of the dying and their families, but also to show the possibilities for social and medical solutions in both a rational (economic) and human manner, without resorting to experiments with euthanasia. Our study was conducted using a diagnostic survey, in which the following techniques were used: an analysis of documents; observation; interview. The observation and interview were conducted in 2011 in two hospices (the St. Lazarus Hospice in Krakow and the St. Brother Albert Hospice in Dąbrowa Tarnowska). Interviews were given to: the management, the volunteer manager, and staff at both institutions. In addition, research on social attitudes towards euthanasia was carried out in the same year in Tarnów (Part 5).
Keywords: incurable disease; cancer; euthanasia